2019
DOI: 10.1038/s41598-019-47096-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating fouling at the pore-scale using a microfluidic membrane mimic filtration system

Abstract: The work investigates fouling in a microfluidic membrane mimic (MMM) filtration system for foulants such as polystyrene particles and large polymeric molecules. Our MMM device consists of a staggered arrangement of pillars which enables real-time visualization and analysis of pore-scale phenomena. Different fouling scenarios are investigated by conducting constant-pressure experiments. Fouling experiments are performed with three different types of foulants: polystyrene particle solution (colloidal fouling), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The presented method of combined pore network simulation and macroscopic modeling is of specific interest in cases of changes of the pore network structure or changes of the liquid and gas distributions during dynamic invasion. It is a generic method that could also be applied for situations where pore and throat sizes vary over time, e.g., as a result of fouling effects or pore blocking resulting from contaminations in the liquid phase [25,[61][62][63]. In such situations, a recursive procedure of alternating simulations is proposed.…”
Section: Macroscopic Continuum Modelmentioning
confidence: 99%
“…The presented method of combined pore network simulation and macroscopic modeling is of specific interest in cases of changes of the pore network structure or changes of the liquid and gas distributions during dynamic invasion. It is a generic method that could also be applied for situations where pore and throat sizes vary over time, e.g., as a result of fouling effects or pore blocking resulting from contaminations in the liquid phase [25,[61][62][63]. In such situations, a recursive procedure of alternating simulations is proposed.…”
Section: Macroscopic Continuum Modelmentioning
confidence: 99%
“…Colloidal fouling of pressure‐driven membranes by silica, clay minerals, aluminum, iron and manganese oxides is also likely to occur if these substances are not disposed of properly. Already, fouling of NF and RO membranes by different colloidal substances has been extensively investigated 6,7 and results have shown that rough and hydrophobic membranes are highly prone to fouling by small colloids such as silica and aluminum 6,8 . Similar to organic fouling, flux decline in colloidal fouling has also been ascribed to the combined effects of an increase in hydraulic resistance imparted by the cake layer and CECP effects.…”
Section: Introductionmentioning
confidence: 99%
“…At higher applied pressure, organic or inorganic particles are forced to pass through the membrane structure. Thus, under this condition, it is anticipated that pore-blocking could occur which leads to a greater accumulation of bacteria and other foulants on the membrane surface 45 , 46 . Moreover, the bacterial attachment would also be greater as the normal shear stress (equivalent to static pressure 47 ) is increased, resulting in higher biofilm thickness, as evident in the OCT scans.…”
Section: Resultsmentioning
confidence: 99%